Activated carbon material as well as preparation method and application thereof

By using the combined treatment of alkaline liquid and wood ash leaching liquid in the preparation process of activated carbon materials, the pore size distribution and surface functional groups of activated carbon are regulated, and the problem of the unsatisfactory VOCs adsorption effect of existing activated carbon materials is solved, achieving more efficient VOCs adsorption and longer penetration time.

CN119771384APending Publication Date: 2025-04-08BEIJING SMARTMI TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510064393.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The adsorption effect of existing activated carbon materials on indoor volatile organic compounds (VOCs) is not ideal, and the penetration time is short.

Method used

By soaking the activated carbon raw material in alkaline liquid and soaking the wood ash leaching solution, combining preheating, calcining and drying steps, the pore size distribution and surface functional groups of the activated carbon are regulated, and its adsorption performance on VOCs is improved.

Benefits of technology

The saturation adsorption capacity and penetration time of activated carbon on VOCs is significantly improved, the adsorption capacity to hydrophobic VOCs is enhanced, and the air purification effect is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005243811120000131
    Figure BDA0005243811120000131
Patent Text Reader

Abstract

The invention relates to the technical field of activated carbon, in particular to an activated carbon material and a preparation method and application thereof. A preparation method of an activated carbon material comprises the following steps: soaking an activated carbon raw material in an alkaline solution and a plant ash leaching solution, carrying out first washing to obtain a first carbon material, preheating the first carbon material, calcining, carrying out second washing, and drying to obtain the activated carbon material. According to the preparation method of the activated carbon material, the activated carbon raw material is treated through the combination of alkaline solution soaking and plant ash leaching solution soaking, the pore size distribution of the activated carbon can be effectively regulated and controlled, the micropore volume distribution proportion and the micropore volume are increased, and the saturated adsorption capacity of the activated carbon to volatile organic compound molecules is increased; hydrophobic modification is carried out on functional groups on the surface of the activated carbon, the adsorption capacity of the activated carbon to hydrophobic volatile organic compound molecules can be enhanced, and the penetration time of the activated carbon to the volatile organic compound molecules is remarkably prolonged through coordination and cooperation of all the steps.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of activated carbon, and in particular to an activated carbon material and a preparation method and application thereof. Background Art

[0002] The control measures for volatile organic compounds (VOCs) in indoor air include the control of pollution sources, the control of pollutant transmission process and active control. In view of the current situation of indoor pollutant sources, controlling the generation of release sources is the most fundamental method to reduce the concentration of indoor VOCs. Green and environmentally friendly building materials, furniture and daily chemical products, and high-performance fume purification equipment can be used to reduce indoor VOCs pollution. For VOCs that are already free in the indoor air, the concentration can be quickly reduced by controlling the transmission of pollutants such as fresh air exchange. However, fresh air exchange consumes a lot of energy, and the purification effect is affected by the quality of outdoor air, and VOCs in indoor air cannot be completely eliminated. Therefore, after taking measures to control pollution sources and pollutant transmission processes, the use of active control technology, that is, continuous purification of indoor VOCs, is one of the most effective means to improve indoor air quality.

[0003] Active control technology mainly includes destruction technology and recovery technology. The destruction technologies mainly include thermal oxidation, catalytic oxidation, plasma, photocatalytic oxidation and biodegradation, and the recovery technologies mainly include adsorption, absorption, condensation and membrane separation.

[0004] Among the destruction technologies, thermal oxidation is suitable for high-flow and high-concentration VOCs purification, and is mainly used for the purification of VOCs in industrial flue gas. More than 99% of VOCs can be decomposed at high temperatures (>1000°C) by thermal oxidation technology, but thermal oxidation technology requires additional fuel and high-temperature resistant equipment. In addition, due to incomplete thermal combustion, toxic byproducts such as dioxins and carbon monoxide are produced in the flue gas of the incinerator, and nitrogen oxides can also be produced in large quantities during high-temperature combustion.

[0005] Catalytic oxidation can be effectively used to treat exhaust gases with different concentrations of VOCs and flow rates, but it is best suited for medium flow rates and low concentrations of VOCs. Common catalysts used for catalytic oxidation are nickel, chromium, copper, and manganese-based materials. In addition, some precious metal catalysts, such as platinum, palladium, gold, and silver, have also attracted widespread attention in the catalytic oxidation of VOCs due to their excellent activity at low temperatures, but in actual use, they are often limited by cost and difficult to popularize.

[0006] Plasma is a highly ionized gas produced by high-voltage discharge, usually composed of electrons, positive ions and neutral particles (atoms or molecules). Plasma is produced under a strong electric field, which bombards organic compounds and destroys their chemical structure, thereby degrading organic matter. In addition, plasma also produces free radicals and oxidizing species, which promote the breaking of chemical bonds of substances such as VOCs, and eventually convert them into CO2 and H2O. However, plasma technology also produces secondary pollutants such as formic acid, carboxylic acid, nitrogen oxides and ozone in the process of purifying VOCs.

[0007] Photocatalytic oxidation technology is a new type of advanced oxidation technology that has rapidly emerged in recent years. After being excited by high-energy photons, photocatalytic materials produce photogenerated electrons and holes, which then produce active species such as OH· and O2- on the catalyst surface, which react with VOCs to undergo mineralization and convert into CO2 and H2O. Photocatalytic oxidation technology is only applicable to low-concentration VOCs and must be able to react under light. In addition, for VOCs with stable structures, the degree of mineralization is incomplete, resulting in secondary pollutants.

[0008] Biodegradation technology requires less energy in the process of purifying VOCs and is suitable for purifying VOCs below 5000ppm. However, the purification cycle is long, and it takes up to 7 months to achieve 100% purification efficiency. In addition, intermediate products such as acetaldehyde, propionaldehyde and acetone are produced, causing secondary pollution to the atmospheric environment.

[0009] Compared with the commonly used VOCs control technologies, adsorption technology is applicable to the lowest pollutant concentration, the reaction temperature is close to room temperature, and the cost of adsorption technology is low, easy to implement, and the reaction speed is fast. In view of the low concentration and long-term volatility of formaldehyde and toluene in indoor environments, adsorption technology is considered to be one of the most efficient indoor formaldehyde and toluene control technologies. However, the adsorption effect of activated carbon materials in the existing technology on VOCs molecules is not ideal, and the penetration time of VOCs molecules is short.

[0010] In view of this, the present invention is proposed. Summary of the invention

[0011] One object of the present invention is to provide a method for preparing an activated carbon material to solve the technical problems in the prior art that the activated carbon material has an unsatisfactory adsorption effect on VOCs molecules and a short penetration time for VOCs molecules.

[0012] Another object of the present invention is to provide an activated carbon material having a suitable micropore ratio, micropore volume and water contact angle, good adsorption effect on VOCs molecules and long penetration time.

[0013] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0014] A method for preparing an activated carbon material comprises the following steps:

[0015] The activated carbon raw material is soaked in alkaline liquid and wood ash leaching liquid, and after a first washing, a first carbon material is obtained. The first carbon material is preheated, calcined, washed for a second time and dried to obtain an activated carbon material.

[0016] In some embodiments, the volume ratio of the activated carbon raw material, the alkaline liquid and the wood ash extract is 1:(2-4):(2-4).

[0017] In some embodiments, the activated carbon raw material includes coal-based columnar activated carbon.

[0018] In some embodiments, the alkaline liquid includes at least one of sodium sulfite, potassium pyrophosphate, potassium carbonate, potassium bicarbonate and potassium phosphate.

[0019] In some embodiments, the concentration of the alkaline solution is 0.01-0.02 mol / L.

[0020] In some embodiments, the soaking time in the alkaline solution is 25 to 60 minutes.

[0021] In some embodiments, the method for preparing the wood ash extract comprises: soaking 6 to 8 parts by mass of wood ash in 100 parts by mass of water for 36 to 48 hours, separating the solid from the liquid, and obtaining the wood ash extract.

[0022] In some implementations, the mass content of potassium in the wood ash extract is 10% to 15%.

[0023] In some implementations, the soaking time of the wood ash extract is 25 to 60 minutes.

[0024] In some embodiments, the pH value of the washing solution after the first washing is 9-11.

[0025] In some implementations, the preheating temperature is 160-240° C., and the preheating time is 8-16 hours.

[0026] In some embodiments, the calcination includes a first constant temperature treatment, a second constant temperature treatment and a third constant temperature treatment performed in sequence, the temperature of the first constant temperature treatment is 680-750°C, the time of the first constant temperature treatment is 20-35 minutes, the temperature of the second constant temperature treatment is 800-870°C, the time of the second constant temperature treatment is 1-3 hours, the temperature of the third constant temperature treatment is 600-670°C, and the time of the third constant temperature treatment is 20-35 minutes.

[0027] In some embodiments, during the calcination process, water vapor is injected every 8 to 12 seconds, and the mass of the water vapor injected each time is 1% to 1.5% of the mass of the calcined activated carbon.

[0028] In some embodiments, the drying temperature is 100 to 150° C., and the drying time is 20 to 48 hours.

[0029] An activated carbon material is prepared by the activated carbon material preparation method.

[0030] In some embodiments, the micropore volume of the activated carbon material accounts for more than 60%, and the micropore volume is greater than 0.4 cm 3 / g, and the water contact angle is 125°~150°.

[0031] In some embodiments, the iodine value of the activated carbon material is 1020-1035 mg / g; the CTC value of the activated carbon material is 73%-78%; and the methylene blue value of the activated carbon material is 11.9-13.5 mg / g.

[0032] The activated carbon material is used as a VOCs adsorbent in air purification. The adsorption capacity of the activated carbon material for VOCs molecules is 363-410 mg / g, and the penetration time of the activated carbon material for VOCs molecules is 329-370 min.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] (1) The preparation method of the activated carbon material of the present invention can effectively control the pore size distribution of the activated carbon by combining alkaline solution immersion and plant ash leaching solution immersion to make the micropore volume distribution account for more than 60% and the micropore volume is more than 0.4 cm 3 / g, which increases the saturated adsorption capacity of activated carbon for VOCs molecules; hydrophobic modification of the surface functional groups of activated carbon can enhance the adsorption capacity of activated carbon for hydrophobic VOCs molecules. Through the coordination of various steps, the penetration time of activated carbon for VOCs molecules is significantly improved.

[0035] (2) The activated carbon material of the present invention has a suitable micropore volume ratio and micropore volume, a large water contact angle, good hydrophobicity, and better adsorption performance for VOCs. It can be used as an adsorbent to purify VOCs gas in the air and effectively improve the air quality. DETAILED DESCRIPTION

[0036] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0037] A method for preparing an activated carbon material, characterized in that it comprises the following steps:

[0038] The activated carbon raw material is soaked in alkaline liquid and wood ash leaching liquid, and after a first washing, a first carbon material is obtained. The first carbon material is preheated, calcined, washed for a second time and dried to obtain an activated carbon material.

[0039] The preparation method of the activated carbon material of the present invention combines the treatment of the activated carbon raw material by soaking in an alkaline liquid and soaking in a wood ash leaching liquid. The alkaline liquid and the wood ash leaching liquid are in full contact with the activated carbon and can be successfully attached to the surface of the activated carbon. During the preheating and high-temperature calcination process, the alkaline liquid and the wood ash leaching liquid successfully attached to the surface of the activated carbon can react with the acidic active functional groups on the surface of the activated carbon, so that the surface properties of the activated carbon are changed; at the same time, the high-temperature calcination process with water vapor can readjust the pore size distribution of the activated carbon; after the changed activated carbon surface is fully contacted with high-temperature water vapor, its hydrophobicity is enhanced. In summary, the preparation method of the present invention can effectively control the pore size distribution of the activated carbon, so that the micropore volume distribution accounts for more than 60%, and the micropore volume is more than 0.4cm 3 / g, which increases the saturated adsorption capacity of activated carbon for VOCs molecules; hydrophobic modification of the surface functional groups of activated carbon can enhance the adsorption capacity of activated carbon for hydrophobic VOCs molecules. Through the coordination of various steps, the penetration time of activated carbon for VOCs molecules is significantly improved.

[0040] In some embodiments, the volume ratio of the activated carbon raw material, the alkaline liquid and the plant ash extract is 1:(2-4):(2-4), including but not limited to 1:2:2, 1:3:3, 1:4:4, etc. The present invention adopts a suitable volume ratio of activated carbon, alkaline liquid and plant ash extract to improve the treatment effect of the activated carbon and enhance the adsorption performance of the activated carbon.

[0041] In some embodiments, the activated carbon raw material includes coal-based columnar activated carbon.

[0042] In some embodiments, the alkaline liquid includes at least one of sodium sulfite, potassium pyrophosphate, potassium carbonate, potassium bicarbonate and potassium phosphate, such as a combination of sodium sulfite and potassium pyrophosphate, a combination of potassium carbonate and potassium bicarbonate, etc. In some embodiments, the concentration of the alkaline liquid is 0.01-0.02 mol / L, including but not limited to 0.01 mol / L, 0.015 mol / L, 0.02 mol / L, etc. In some embodiments, the soaking time of the alkaline liquid is 25-60 min, including but not limited to 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min, etc. The appropriate soaking time of the alkaline liquid can better regulate the pore size of the activated carbon and improve its adsorption performance.

[0043] In some embodiments, the preparation method of the plant ash extract specifically comprises: soaking 6 to 8 parts by mass of plant ash in 100 parts by mass of water for 36 to 48 hours, separating the solid and the liquid, and obtaining the plant ash extract. In some embodiments, the plant ash is 6 parts by mass, 6.5 parts by mass, 7 parts by mass, 7.5 parts by mass, and 8 parts by mass. The soaking time is 36 hours, 40 hours, 42 hours, 45 hours, 48 ​​hours, etc. In some embodiments, the mass content of potassium in the plant ash extract is 10% to 15%, such as 10%, 10.5%, 11%, 12%, 13%, 14%, or 15%. In some embodiments, the soaking time of the plant ash extract is 25 to 60 minutes, such as 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes, or 60 minutes. The activated carbon soaked in alkaline liquid is treated with the plant ash leaching liquid of the present invention, so as to further adjust the water properties of the activated carbon and improve the adsorption performance of VOCs.

[0044] In some embodiments, the pH value of the first washing eluate is 9-11, such as 9, 9.5, 10, 10.5, 11, etc.

[0045] In some embodiments, the first carbon material is dried and then preheated. The preheating temperature is 160-240°C, including but not limited to 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, etc. The preheating time is 8-16h, such as 8h, 9h, 10h, 11h, 12h, 13h, 14h or 16h, etc.

[0046] In some embodiments, calcination includes a first constant temperature treatment, a second constant temperature treatment and a third constant temperature treatment performed sequentially, the temperature of the first constant temperature treatment is 680-750°C, such as 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, etc., and the time of the first constant temperature treatment is 20-35 minutes, such as 20 minutes, 22 minutes, 25 minutes, 30 minutes or 35 minutes, etc. The temperature of the second constant temperature treatment is 800-870°C, such as 800°C, 810°C, 820°C, 840°C, 850°C, etc., and the time of the second constant temperature treatment is 1-3 hours, such as 1 hour, 1.5 hours, 2 hours, 3 hours, etc. The temperature of the third constant temperature treatment is 600-670°C, such as 600°C, 610°C, 620°C, 650°C, etc., and the time of the third constant temperature treatment is 20-35min, such as 10min, 15min, 20min, 25min, 30min or 35min, etc. In some embodiments, during the calcination process, water vapor is injected every 8-12s (such as 8s, 10s or 12s), and the mass of each injected water vapor is 1%-1.5% of the mass of the calcined activated carbon, such as 1%, 1.1%, 1.2%, 1.3% or 1.5%, etc. The present invention adopts the above-mentioned suitable calcination conditions to ensure that the activated carbon has a suitable pore volume, so that it has excellent structural stability and adsorption performance.

[0047] In some embodiments, the second washing is performed 2 to 4 times.

[0048] In some embodiments, the drying temperature is 100-150°C, for example, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, etc., and the drying time is 20-48h, for example, 20h, 25h, 30h, 36h, 40h, 45h or 48h, etc.

[0049] According to another aspect of the present invention, the present invention also relates to an activated carbon material prepared by the above-mentioned method for preparing the activated carbon material.

[0050] The activated carbon material of the present invention has a suitable micropore ratio, micropore volume and water contact angle. In some embodiments, the micropore volume ratio of the activated carbon material is greater than 60%, such as 65%, 70%, 75%, 80%, 85%, 90%, 95%, etc., or any range between the two; the micropore volume is greater than 0.4 cm 3 / g, for example 0.45cm 3 / g, 0.5cm 3 / g, 0.55cm 3 / g, or any range value therebetween; the water contact angle is 125° to 150°, for example, 125°, 130°, 135°, 140°, 145°, 150°, etc.

[0051] In some embodiments, the iodine value of the activated carbon material is 1020-1035 mg / g, such as 1020 mg / g, 1025 mg / g, 1030 mg / g, 1035 mg / g, etc. The CTC value of the activated carbon material is 73%-78%, such as 73%, 74%, 75%, 76%, 77% or 78%, etc. The methylene blue of the activated carbon material is 11.9-13.5 mg / g, such as 11.9 mg / g, 12 mg / g, 12.5 mg / g, 13 mg / g or 13.5 mg / g, etc. The penetration time of the activated carbon material is 329-370 min, such as 329 min, 330 min, 350 min, 360 min or 370 min, etc.

[0052] According to another aspect of the present invention, the present invention also relates to the use of the above activated carbon material as a VOCs adsorbent in air purification, and the adsorption capacity of VOCs by the activated carbon material is 363-410 mg / g, for example, 370 mg / g, 375 mg / g, 380 mg / g, 385 mg / g or 390 mg / g, etc.

[0053] In some embodiments, the VOCs include at least one of toluene, xylene, butyl acetate, and styrene.

[0054] The following is further explained in conjunction with specific embodiments and comparative examples.

[0055] Example 1

[0056] A method for preparing an activated carbon material comprises the following steps:

[0057] (1) Place a 2 mm activated carbon raw material in a 0.015 mol / L sodium sulfite solution (alkaline liquid) and soak for 30 minutes; then soak it in a wood ash extract for 30 minutes. Preparation of the wood ash extract: soak 7 parts by mass of wood ash in 100 parts by mass of water for 40 hours, separate the solid and the liquid, and obtain the wood ash extract. The mass content of potassium in the wood ash extract is 12%; the volume ratio of the above-mentioned activated carbon raw material, alkaline liquid, and wood ash extract is 1:3:3; after soaking, wash it with clean water for 3 times until the pH value of the eluate is 9.5. After washing, dry it to obtain the first carbon material.

[0058] (2) The dried first carbon material is placed in an oven at 200° C. for 12 hours.

[0059] (3) The dried activated carbon was placed in a high-temperature furnace for high-temperature calcination at 700°C for 30 minutes, then gradually increased to 850°C for 2 hours, and then gradually reduced to 650°C for 30 minutes. Water vapor was injected every 10 seconds, and the injection amount was 1.2% of the amount of activated carbon.

[0060] After completion, the product was cooled, washed with water, and then dried at 125°C for 24 hours. After cooling, the final activated carbon material was obtained.

[0061] Example 2

[0062] A method for preparing an activated carbon material comprises the following steps:

[0063] (1) Place a 2 mm activated carbon raw material in a 0.015 mol / L potassium pyrophosphate solution and soak for 30 minutes; then soak it in a wood ash extract for 30 minutes. Preparation of the wood ash extract: soak 7 parts by mass of wood ash in 100 parts by mass of water for 40 hours, separate the solid and liquid, and obtain the wood ash extract. The mass content of potassium in the wood ash extract is 12%; the volume ratio of the above activated carbon raw material, alkaline liquid, and wood ash extract is 1:3:3; after soaking, wash it with clean water for 3 times until the pH value of the extract is 9.5, and dry it after washing to obtain the first carbon material.

[0064] (2) The dried first carbon material is placed in an oven at 200° C. for 12 hours.

[0065] (3) The dried activated carbon was placed in a high temperature furnace for high temperature calcination, calcined at 700°C for 30 minutes, then gradually increased to 850°C for 2 hours, and then gradually reduced to 650°C for 30 minutes, and water vapor was injected every 10 seconds, and the injection amount was 1.2% of the amount of activated carbon. After completion, it was cooled, washed with water, and then dried at 110°C for 36 hours. After cooling, the final activated carbon material was obtained.

[0066] Example 3

[0067] A method for preparing an activated carbon material comprises the following steps:

[0068] (1) Place a 2 mm activated carbon raw material in a 0.015 mol / L sodium sulfite / potassium phosphate mixed solution (the molar ratio of sodium sulfite to potassium phosphate is 3:1) and soak for 30 minutes; then soak in a wood ash extract for 30 minutes. Preparation of the wood ash extract: soak 7 parts by mass of wood ash in 100 parts by mass of water for 40 hours, separate the solid and liquid, and obtain the wood ash extract. The mass content of potassium in the wood ash extract is 12%; the volume ratio of the above-mentioned activated carbon raw material, alkaline liquid, and wood ash extract is 1:3:3; after soaking, wash with clean water 3 times to a pH value of 9.5. After washing, dry it to obtain the first carbon material.

[0069] (2) The dried first carbon material is placed in an oven at 200° C. for 12 hours.

[0070] (3) The dried activated carbon was placed in a high temperature furnace for high temperature calcination, calcined at 700°C for 30 minutes, then gradually increased to 850°C for 2 hours, and then gradually reduced to 650°C for 30 minutes, and water vapor was injected every 10 seconds, and the injection amount was 1.2% of the amount of activated carbon. After completion, it was cooled, washed with water, and then dried at 125°C for 24 hours. After cooling, the final activated carbon material was obtained.

[0071] Example 4

[0072] A method for preparing an activated carbon material comprises the following steps:

[0073] (1) Place a 2 mm activated carbon raw material in a 0.015 mol / L sodium sulfite / potassium phosphate mixed solution (the molar ratio of sodium sulfite to potassium phosphate is 3:1) and soak for 45 minutes; then soak in a wood ash extract for 45 minutes. Preparation of the wood ash extract: soak 7 parts by mass of wood ash in 100 parts by mass of water for 40 hours, separate the solid and liquid, and obtain the wood ash extract. The mass content of potassium in the wood ash extract is 12%; the volume ratio of the above-mentioned activated carbon raw material, alkaline liquid, and wood ash extract is 1:3:3; after soaking, wash with clean water 3 times to a pH value of 9.5 for the extract, and dry it after washing to obtain the first carbon material.

[0074] (2) The dried first carbon material is placed in an oven at 200° C. for 12 hours.

[0075] (3) The dried activated carbon was placed in a high temperature furnace for high temperature calcination, calcined at 700°C for 30 minutes, then gradually increased to 850°C for 2 hours, and then gradually reduced to 650°C for 30 minutes, and water vapor was injected every 10 seconds, and the injection amount was 1.2% of the amount of activated carbon. After completion, it was cooled, washed with water, and then dried at 125°C for 24 hours. After cooling, the final activated carbon material was obtained.

[0076] Example 5

[0077] A method for preparing an activated carbon material comprises the following steps:

[0078] (1) Place a 2 mm activated carbon raw material in a 0.01 mol / L sodium sulfite solution and soak for 60 minutes; then soak it in a wood ash extract for 45 minutes. Preparation of the wood ash extract: soak 7 parts by mass of wood ash in 100 parts by mass of water for 36 hours, separate the solid and the liquid, and obtain the wood ash extract. The mass content of potassium in the wood ash extract is 10%; after the soaking is completed, wash it with clean water for 3 times until the pH value of the extract is 10, and dry it after washing to obtain the first carbon material.

[0079] (2) The dried first carbon material is placed in an oven at 160° C. for 16 hours.

[0080] (3) The dried activated carbon was placed in a high temperature furnace for high temperature calcination, calcined at 680°C for 35 minutes, then gradually increased to 800°C for 3 hours, and then gradually reduced to 600°C for 35 minutes, and water vapor was injected every 10 seconds, and the injection amount was 1.5% of the amount of activated carbon. After completion, it was cooled, washed with water, and then dried at 150°C for 20 hours. After cooling, the final activated carbon material was obtained.

[0081] Example 6

[0082] A method for preparing an activated carbon material comprises the following steps:

[0083] (1) Place a 2 mm activated carbon raw material in a 0.02 mol / L sodium sulfite solution and soak for 25 min; then soak it in a wood ash extract for 60 min. Preparation of the wood ash extract: soak 7 parts by mass of wood ash in 100 parts by mass of water for 48 h, separate the solid and liquid, and obtain the wood ash extract. The mass content of potassium in the wood ash extract is 15%; after the soaking is completed, wash it with clean water for 3 times until the pH value of the extract is 11. After washing, dry it to obtain the first carbon material.

[0084] (2) The dried first carbon material is placed in an oven at 240° C. for 8 hours.

[0085] (3) The dried activated carbon is placed in a high temperature furnace for high temperature calcination, calcined at 750°C for 20 minutes, then gradually raised to 870°C for 1 hour, and then gradually lowered to 670°C for 20 minutes, and water vapor is injected every 10 seconds, and the injection amount is 1% of the amount of activated carbon. After completion, it is cooled, washed with water, and then dried at 100°C for 30 hours. After cooling, the final activated carbon material is obtained.

[0086] Comparative Example 1

[0087] A method for preparing an activated carbon material, which is different from Example 1 in that:

[0088] Sodium sulfite solution is not used for soaking.

[0089] Comparative Example 2

[0090] A method for preparing an activated carbon material, which is different from Example 1 in that:

[0091] No wood ash extract is used for soaking.

[0092] Comparative Example 3

[0093] 2mm activated carbon raw material.

[0094] Experimental example

[0095] The iodine value, CTC value, methylene blue value and adsorption amount of VOCs mixed gas of the activated carbon materials of each embodiment and comparative example were tested. The VOCs gas used was the gas generated by air passing through a gas washing bottle filled with toluene.

[0096] The basic principle of the dynamic adsorption test is to pass the initial VOCs gas with a certain humidity through a reaction bed filled with activated carbon at a specific flow rate, and continuously monitor the concentration of VOCs in the exhaust gas. When the exhaust gas concentration remains unchanged within 30 minutes and is more than 80% of the initial concentration, it is considered to be adsorption penetration.

[0097] Table 1 Test results

[0098]

[0099] As shown in Table 1, the micropore volume of the activated carbon material obtained by the methods of each embodiment of the present invention is suitable, ranging from 0.42 to 0.56 cm 3 / g, the water contact angle is suitable, the water contact angle is 125°~150°, the methylene blue value is 11.9~13.5mg / g, the CTC value is 73%~78%, the adsorption amount of toluene is 363~402mg / g, the penetration time is 329~370min, it has a higher saturated adsorption capacity for VOCs and has a good adsorption effect.

[0100] The activated carbon materials of Comparative Examples 1 to 3 have relatively lower micropore volumes, smaller water contact angles, significantly less toluene adsorption than Example 1 of the present invention, shorter penetration times, and poorer adsorption performance.

[0101] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing an activated carbon material, characterized in that: The following steps are involved: The activated carbon raw material is soaked in alkaline liquid and wood ash leaching liquid, and after a first washing, a first carbon material is obtained. The first carbon material is preheated, calcined, washed for a second time and dried to obtain an activated carbon material.

2. The method for preparing an activated carbon material according to claim 1, characterized in that: Contains at least one of the following features (1) to (2): (1) The volume ratio of the activated carbon raw material, the alkaline liquid and the wood ash extract is 1:(2-4):(2-4); (2) The activated carbon raw material includes coal-based columnar activated carbon.

3. The method for preparing an activated carbon material according to claim 1, characterized in that: Contains at least one of the following features (1) to (3): (1) The alkaline liquid includes at least one of sodium sulfite, potassium pyrophosphate, potassium carbonate, potassium bicarbonate and potassium phosphate; (2) The concentration of the alkaline solution is 0.01 to 0.02 mol / L; (3) The soaking time in the alkaline solution is 25 to 60 minutes.

4. The method for preparing an activated carbon material according to claim 1, characterized in that: Contains at least one of the following features (1) to (3): (1) The method for preparing the plant ash extract comprises: soaking 6 to 8 parts by weight of plant ash in 100 parts by weight of water for 36 to 48 hours, separating the solid from the liquid, and obtaining the plant ash extract; (2) The mass content of potassium in the wood ash extract is 10% to 15%; (3) The soaking time of the wood ash extract is 25 to 60 minutes.

5. The method for preparing an activated carbon material according to claim 1, characterized in that: Contains at least one of the following features (1) to (2): (1) the first washing is performed until the pH value of the washing solution is 9 to 11; (2) The preheating temperature is 160-240° C., and the preheating time is 8-16 hours.

6. The method for preparing an activated carbon material according to claim 1, characterized in that: Contains at least one of the following features (1) to (2): (1) The calcination includes a first constant temperature treatment, a second constant temperature treatment and a third constant temperature treatment performed in sequence, wherein the temperature of the first constant temperature treatment is 680-750° C., the time of the first constant temperature treatment is 20-35 min, the temperature of the second constant temperature treatment is 800-870° C., the time of the second constant temperature treatment is 1-3 h, the temperature of the third constant temperature treatment is 600-670° C., and the time of the third constant temperature treatment is 20-35 min; (2) During the calcination process, water vapor is injected every 8 to 12 seconds, and the mass of the water vapor injected each time is 1% to 1.5% of the mass of the calcined activated carbon.

7. The method for preparing an activated carbon material according to claim 1, characterized in that: The drying temperature is 100-150° C., and the drying time is 20-48 hours.

8. An activated carbon material, characterized in that The activated carbon material is prepared by the method for preparing the activated carbon material according to any one of claims 1 to 7.

9. The activated carbon material according to claim 8, characterized in that Contains at least one of the following features (1) to (5): (1) The micropore volume of the activated carbon material accounts for more than 60%, and the micropore volume is 0.4 to 0.6 cm 3 / g; (2) The water contact angle of the activated carbon material is 125° to 150°; (3) The iodine value of the activated carbon material is 1020-1035 mg / g; (4) The CTC value of the activated carbon material is 73% to 78%; (5) The methylene blue content of the activated carbon material is 11.9 to 13.5 mg / g.

10. Use of the activated carbon material according to claim 8 or 9 as a VOCs adsorbent in air purification, wherein the adsorption capacity of the activated carbon material for VOCs molecules is 363-410 mg / g, and the penetration time of the activated carbon material for VOCs molecules is 329-370 min.